India in the new world order: The changing contours of her foreign policy under Narendra Modi - Edited by Kothari, Raj Kumar (New Delhi Atlantic Publishers and Distributers, 2021)
Given the intricacies involved in the arena of world politics, no state can isolate itself from its involvement in the international sphere. This involvement must be premised on well-defined principles that aim to advance national interests of the concerned independent sovereign state. Perhaps that is why every single state needs to have a well-defined foreign policy framework consisting of purposes and principles based on which it formulates policy towards other states and actors. India is no exception.As India under the leadership of Narendra Modi aims to achieve the status of an and lsquo;emergent' power, it confronts numerous challenges from multiple corners. In this backdrop, the present volume seeks to assess the trends and directions of India's foreign policy in the post-cold war years with special emphasis on the tenure of Narendra Modi.The book has been very timely and would be of immense help to policy makers, diplomats, researchers and academia in general.
Keywords: Prime Minister; Indian Foreign Policy; Indian Politics